Formal education/popular education: dynamics regarding adaptation and resistance to modernity. Experience studied in the province of Guanacaste, Costa Rica (2012-2013) - Herra Castro, Ernesto (2016)
The author discusses the logic and the domain’s vertical order in modernity, as well as its concrete expression in the Costa Rican educational dynamics. The paper shows the existing tension between formal education and the possible freedom and detachment from the imposed order in modernity pursued and promoted by popular education. This is done based on the project entitled “Critical Literacy in School Culture: Society and Human Rights” executed in Guanacaste.